2000
DOI: 10.1260/0263617001493242
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory Adsorption as the Determinant of the Fluctuating Behaviour of Different Heterogeneous Systems

Abstract: Heterogeneous, catalytic oscillatory reactions as well as the oscillatory process of complex formation based on solid urea have been analysed in an attempt to ascertain the cause of such oscillatory mechanisms. In this context, oscillatory adsorption/desorption, phase transitions of the supported metal employed as the catalyst in the relevant oscillatory oxidation-reduction reactions as well as the reactions themselves have been considered.Based on an analysis of two oscillatory systems, of which one (i.e. the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…3, Table 2). The ratio of R 560/440 of band intensities for samples synthesized from MOR zeolite decreases monotonically with increasing content of nickel in the samples compared to the original NaMOR from 100 % to 85%, which obviously indicates a slight destruction of the crystal structure (up to 15%) in the process of applying a large amount of metal component (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) wt. %) on zeolite of this structural type.…”
Section: Fig 2 Ir Spectra Of Catalysts On Mordenite Base: 1 -Namor; 2 -Hmor-im1ni; 3 -Hmor-im5ni; 4 -Hmor-im15nimentioning
confidence: 97%
See 1 more Smart Citation
“…3, Table 2). The ratio of R 560/440 of band intensities for samples synthesized from MOR zeolite decreases monotonically with increasing content of nickel in the samples compared to the original NaMOR from 100 % to 85%, which obviously indicates a slight destruction of the crystal structure (up to 15%) in the process of applying a large amount of metal component (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) wt. %) on zeolite of this structural type.…”
Section: Fig 2 Ir Spectra Of Catalysts On Mordenite Base: 1 -Namor; 2 -Hmor-im1ni; 3 -Hmor-im5ni; 4 -Hmor-im15nimentioning
confidence: 97%
“…[1][2][3][4]. Being the materials with unique properties [5][6][7] they are the effective catalysts and sorbents, in particular, they have high efficiency towards extraction of heavy and radioactive metals from the aqua medium [8][9][10][11]. The most used in industry are LTA, FAU, MFI, and MOR-type zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…Since during the conversion of carbohydrates over zeolite catalysts two competing processes of the conversion of hexoses into 5-HMF and oligomerization to humins simultaneously proceeds, this reaction is similar to the alkylation of isobutane with butenes over acid catalysts, which also involves two competing reactions of isobutane alkylation and butenes oligomerization. 42 It was previously found that the proceeding of alkylation in the oscillating mode allows increasing the time of effective work of the catalyst. It is possible that similarly with alkylation, in the case of conversion of simple carbohydrates, the proceeding of the reaction in the oscillation regime could also be a promising way to increase the efficiency and selectivity of the target process.…”
Section: Catalytic Reactionmentioning
confidence: 99%